I Appreciate You: A Spectral Reading of SoTL during COVID-19 - Facciolo, Laura (Teaching and Learning Inquiry, 2023)
What lives amongst loss? This study employs spectral reading practice to thematically analyze the scholarship of teaching and learning (SoTL) produced within the Canadian blogosphere during the COVID-19 pandemic. Despite the extent of loss that the pandemic brought, the findings of this study reveal that SoTL practitioners continued to embrace positive affectivities and “what works” in their reflective research about the experience of teaching and learning during crisis times. The four revealed themes—endless possibilities, teaching as care, care ethics, and community awe—point towards a hardening disciplinary and methodological characterization of SoTL (or what I refer to as a “SoTL attitude”) that is rooted in qualities of appreciation, generosity, and reparation. Overall, this work contributes to examinations of SoTL as an evolving disciplinary area, providing unique insights into its surprisingly cohesive response to the COVID-19 pandemic. Read the corresponding ISSOTL blog post here.